Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

First they grouped all the "like" terns together and ended up with the equation z = x? Answer: Only statement 2 is sufficient by itself. B

Why? I would have answered A because I plugged in the numbers given in statement 1 and solved for z. Then I came up with z = 2. Then I plugged in the numbers for all 3 variables in the original equation (including z = 2) with the result of left side of equation = right side of equation so I can clearly answer the question with statement 1?

First they grouped all the "like" terns together and ended up with the equation z = x? Answer: Only statement 2 is sufficient by itself. B

Why? I would have answered A because I plugged in the numbers given in statement 1 and solved for z. Then I came up with z = 2. Then I plugged in the numbers for all 3 variables in the original equation (including z = 2) with the result of left side of equation = right side of equation so I can clearly answer the question with statement 1?

Hi,

you have to find if \(\frac{3x}{2}+ y + 2z = \frac{7x}{2}+ y?\)... But there are three variables and 'z' does not cancel out but remains till end.. so we cannot sove the equation. we donot have to find z=2, we should be given z=2 for equation to be correct.. remember it is asking you IS A=B.. so you require both A and B
_________________

First they grouped all the "like" terns together and ended up with the equation z = x? Answer: Only statement 2 is sufficient by itself. B

Why? I would have answered A because I plugged in the numbers given in statement 1 and solved for z. Then I came up with z = 2. Then I plugged in the numbers for all 3 variables in the original equation (including z = 2) with the result of left side of equation = right side of equation so I can clearly answer the question with statement 1?

Notice that the question asks is 3x/2 + y + 2z = 7x/2 + y? Which can be simplified to is z = x? We are NOT given that z = x, we are asked to find whether it's true.

(1) says that x = 2. So the question becomes is x = 2. We don't know that, thus the statement is not sufficient.

(2) says that z = -x. Now, if z = -x, then z = x can only be true when z = x = 0. Since we are told that xyz ≠ 0, then none of the variables is 0, therefore we can say that z ≠ x. Sufficient.

So z = 2 results from the equation with the provided values for x and y and if I plug in all 3 values now I can see that both equation are the same so z = 2 and x = 2 thus z = x

First they grouped all the "like" terns together and ended up with the equation z = x? Answer: Only statement 2 is sufficient by itself. B

Why? I would have answered A because I plugged in the numbers given in statement 1 and solved for z. Then I came up with z = 2. Then I plugged in the numbers for all 3 variables in the original equation (including z = 2) with the result of left side of equation = right side of equation so I can clearly answer the question with statement 1?

Hi,

you have to find if \(\frac{3x}{2}+ y + 2z = \frac{7x}{2}+ y?\)... But there are three variables and 'z' does not cancel out but remains till end.. so we cannot sove the equation. we donot have to find z=2, we should be given z=2 for equation to be correct.. remember it is asking you IS A=B.. so you require both A and B

So z = 2 results from the equation with the provided values for x and y and if I plug in all 3 values now I can see that both equation are the same so z = 2 and x = 2 thus z = x

First they grouped all the "like" terns together and ended up with the equation z = x? Answer: Only statement 2 is sufficient by itself. B

Why? I would have answered A because I plugged in the numbers given in statement 1 and solved for z. Then I came up with z = 2. Then I plugged in the numbers for all 3 variables in the original equation (including z = 2) with the result of left side of equation = right side of equation so I can clearly answer the question with statement 1?

Hi,

you have to find if \(\frac{3x}{2}+ y + 2z = \frac{7x}{2}+ y?\)... But there are three variables and 'z' does not cancel out but remains till end.. so we cannot sove the equation. we donot have to find z=2, we should be given z=2 for equation to be correct.. remember it is asking you IS A=B.. so you require both A and B

We don't know whether 3x/2 + y + 2z = 7x/2 + y. We are asked to find out whether 3x/2 + y + 2z = 7x/2 + y. Please read my reply above.
_________________

Re: If xyz ≠ 0, is 3x/2 + y + 2z = 7x/2 + y? [#permalink]

Show Tags

13 May 2016, 09:52

The question asked is effectively, as Divya pointed out is if x=y which is the simplified version of the equations in questions. only statement 2 answers this.

Re: If xyz ≠ 0, is 3x/2 + y + 2z = 7x/2 + y? [#permalink]

Show Tags

06 Jun 2017, 21:05

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

First they grouped all the "like" terns together and ended up with the equation z = x? Answer: Only statement 2 is sufficient by itself. B

Why? I would have answered A because I plugged in the numbers given in statement 1 and solved for z. Then I came up with z = 2. Then I plugged in the numbers for all 3 variables in the original equation (including z = 2) with the result of left side of equation = right side of equation so I can clearly answer the question with statement 1?

Rewrite and see the pattern here

Essentially 3x/2 +2x + y = 7x/2 + Y

This would mean that X would have to be equal to Y, x=y beccause

3x/2 +4x/2 + y = 7x/2 + Y

St 1

Clearly Insuff because we know nothing about Z

St 2

-x/2 + y 7x/2 +y = this could only be true if X were 0 but neither x nor y nor z can be 0